Spatial-Related Community Structure and Dynamics in Phytoplankton of the Ross Sea, Antarctica - Bolinesi, Francesco; Saggiomo, Maria; Ardini, Francisco; Castagno, Pasquale; Cordone, Angelina; Fusco, Giannetta; Rivaro, Paola; Saggiomo, Vincenzo; Mangoni, Olga (Frontiers in Marine Science, 2020)
The Ross Sea exhibits the largest continental shelf and it is considered to be the most productive region in Antarctica, with phytoplankton communities that have so far been considered to be driven by the seasonal dynamics of the polynya, producing the picture of what is considered as the classical Antarctic food web. Nevertheless, the Ross Sea is made up of a complex mosaic of sub-systems, with physical, chemical, and biological features that change on different temporal and spatial scales. Thus, we investigated the phytoplankton community structure of the Ross Sea with a spatial scale, considering the different ecological sub-systems of the region. The total phytoplankton biomass, maximum quantum efficiency (Fv/Fm), size classes, and main functional groups were analyzed in relation to physical-chemical properties of the water column during the austral summer of 2017. Data from our study showed productivity differences between polynyas and other areas, with high values of biomass in Terra Nova Bay (up to 272 mg chl a m-2) and the south-central Ross Sea (up to 177 mg chl a m-2) that contrast with the HNLC nature of the off-shore waters during summer. Diatoms were the dominant group in all the studied subsystems (relative proportion ≥ 50%) except the southern one, where they coexisted with haptophytes with a similar percentage. Additionally, the upper mixed layer depth seemed to influence the level of biomass rather than the dominance of different functional groups. However, relatively high percentages of dinoflagellates (~30%) were observed in the area near Cape Adare. The temporal variability observed at the repeatedly-sampled stations differed among the sub-systems, suggesting the importance of Long-Term Ecological Research (L-TER) sites in monitoring and studying the dynamics of such an important system for the global carbon cycle as the Ross Sea. Our results provide new insights into the spatial distribution and structure of phytoplankton communities, with different sub-systems following alternative pathways for primary production, identifiable by the use of appropriate sampling scales.